2012
DOI: 10.1016/j.neuron.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Slit/Robo Signaling Modulates the Proliferation of Central Nervous System Progenitors

Abstract: SUMMARY Neurogenesis relies on a delicate balance between progenitor maintenance and neuronal production. Progenitors divide symmetrically to increase the pool of dividing cells. Subsequently, they divide asymmetrically to self-renew and produce new neurons or, in some brain regions, intermediate progenitor cells (IPCs). Here we report that central nervous system progenitors express Robo1 and Robo2, receptors for Slit proteins that regulate axon guidance, and that absence of these receptors or their ligands le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(136 citation statements)
references
References 71 publications
10
119
3
Order By: Relevance
“…The very small numbers of cells that escape this norm are cells expressing high levels of one gene and very low levels of the other (Arai et al, 2011), which given the linearity of the progenitor cell lineage in mouse cortex, these cells have been interpreted as aRGCs beginning to downregulate Pax6 and upregulate Tbr2, in transition to becoming IPCs (Arai et al, 2011). This is indeed coincident with the brief period when newborn IPCs retract the apical process inherited from their mother aRGC to become multipolar cells in SVZ (Borrell et al, 2012; Noctor et al, 2008). The seemingly mutual exclusivity of Pax6 and Tbr2 expression in mouse suggests a relationship of transcriptional repression (Sansom et al, 2009).…”
Section: Molecular Regulation: Evo‐devo Lessons From Transcriptomicsmentioning
confidence: 77%
See 1 more Smart Citation
“…The very small numbers of cells that escape this norm are cells expressing high levels of one gene and very low levels of the other (Arai et al, 2011), which given the linearity of the progenitor cell lineage in mouse cortex, these cells have been interpreted as aRGCs beginning to downregulate Pax6 and upregulate Tbr2, in transition to becoming IPCs (Arai et al, 2011). This is indeed coincident with the brief period when newborn IPCs retract the apical process inherited from their mother aRGC to become multipolar cells in SVZ (Borrell et al, 2012; Noctor et al, 2008). The seemingly mutual exclusivity of Pax6 and Tbr2 expression in mouse suggests a relationship of transcriptional repression (Sansom et al, 2009).…”
Section: Molecular Regulation: Evo‐devo Lessons From Transcriptomicsmentioning
confidence: 77%
“…Newly generated IPCs undergo a transition phase of a few hours when they translocate their cell soma to the VZ but retain an apical process anchored in the apical adherens junction belt, likely inherited from their mother aRGC (Borrell et al, 2012; Noctor et al, 2008; Wilsch‐Bräuniger et al, 2012). The prompt retraction of this apical process and full delamination of IPCs from the VZ is critical for their cell cycle progression and depends on the action of Robo receptors, which in part mediate the downregulation of N‐Cadherin (Borrell et al, 2012; Wong et al, 2012). Once in the SVZ, IPCs undergo mostly symmetric neurogenic divisions, that is one self‐consuming division to produce two neurons (Attardo et al, 2008; Haubensak et al, 2004; Miyata et al, 2004; Noctor et al, 2004).…”
Section: Progenitor Cells In the Developing Mouse Cerebral Cortexmentioning
confidence: 99%
“…PlexinA1 has also recently been shown to modulate Slit signaling (Delloye‐Bourgeois et al, 2015). We and others have shown that Slit–Robo signaling plays a role in neurogenic events within the developing forebrain (Borrell et al, 2012; Yeh et al, 2014). These findings raise the possibility that PlexinA1 might also modulate Slit signaling during corticogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, several chemotropic factors such as Sonic Hedgehog, Netrin, Slit and Wnt family members are expressed in the floor plate or the roof plate during neurogenesis, some of which being detected in the CSF 47 . Slit members have been shown to promote the proliferation of neural progenitors in the cortex 48 . These secreted factors could contribute to the orientation of progenitor division in a redundant manner.…”
Section: Discussionmentioning
confidence: 99%